Factors affecting the provision of high-quality postnatal care services in Zanzibar: a qualitative study - Anna Öjendal; Herborg Holter; Helen Elden; Sanura Salim; Malin Bogren (BMC, 2023)
Abstract Background In Sub-Saharan Africa, the postnatal period is associated with high mortality and accounts for a substantial proportion of maternal deaths. Although postnatal care has been identified as critical in reducing maternal mortality, the quality of care provided is often inadequate. Tanzania and Zanzibar have not made sufficient progress towards achieving the Sustainable Development Goals on maternal health, and there is limited knowledge about the utilization and quality of postnatal follow-up. The aim of this study was therefore to explore factors affecting the provision of high-quality postnatal care services in the urban area of Zanzibar. Methods Five focus group discussions were performed in Swahili with 25 healthcare providers from primary healthcare units in urban Zanzibar. Interviews were audio-recorded, transcribed verbatim, translated into English, and analysed using qualitative content analysis with an inductive approach. Results Factors affecting provision of high-quality postpartum care services could be divided into three generic categories. Difficulty achieving high attendance comprised three subcategories: long waiting times, low awareness among women, and out-of-pocket payment. Lack of basic resources also comprised three subcategories: shortage of healthcare providers, lack of adequate space, and inadequate medical equipment. Insufficient care routines comprised two subcategories: lack of guidelines and deficient chain of information. Conclusions The present findings suggest that the women's perceptions of postnatal care do not align with the intended purpose of routine postnatal care. Instead, the postnatal period primarily leads to visits to health facilities only when urgent care is required, and there is a lack of awareness about the importance of postnatal care. Moreover, limited resources, including equipment, staff, and space, as well as long waiting times, hinder the delivery of high-quality care and contribute to a negative reputation of postnatal care services. To effectively reach all women and improve postnatal care, it is necessary to increase basic resources, modify health education approaches, and enhance the flow of information between different levels of care using context-specific strategies.